ЖОҚАРЫ КЛАСС ОҚЫЎШЫЛАРЫНЫҢ ОҚЫЎДАН ТЫС ИСКЕРЛИГИНДЕГИ ҲУҚЫҚЫЙ ТӘРБИЯСЫНЫҢ ӨЗГЕШЕЛИКЛЕРИ - ДЖамилова, Г.Ж. (ILIM hám JÁMIYET, 2020)
This article discusses the differences in the legal education of high school students in extracurricular activities and the importance of shaping their legal culture and legal education.